Persistent organic pollutants and related biological responses measured in coastal fish using chemical and biological screening methods. Issue 16 (17th September 2017) - Tairova, Zhanna; Strand, Jakob; Bossi, Rossana; Larsen, Martin M.; Förlin, Lars; Bignert, Anders; Hedman, Jenny; Gercken, Jens; Lang, Thomas; Fricke, Nicolai F.; Asmund, Gert; Long, Manhai; et al.
ABSTRACT: The aim of this study was to investigate the spatial distribution, levels of dioxin-like compounds (DLC), and biological responses in two fish species. The viviparous eelpout ( Zoarces viviparus ) was collected from various locations in the Baltic Sea and in fjords of Kattegat and Skagerrak, while shorthorn sculpin ( Myoxocephalus scorpius ) was obtained at the polychlorinated biphenyl (PCB) polluted site in North West Greenland. Significant differences were detected both in contaminant levels and relative contributions from either polychlorinated dibenzodioxins (PCDD) or polychlorinated dibenzofurans (PCDF or furans) and mono-ortho- and non-ortho (coplanar) polychlorinated biphenyls (dl-PCB). Fish from the eastern Baltic Sea generally displayed higher contributions from PCDD/F compared to dl-PCB, whereas dl-PCB were generally predominated in fish from Danish, Swedish, and German sites. Levels of dl-PCB in muscle tissues were above OSPAR environmental assessment criteria (EAC) for PCB118, indicating a potential risk of adverse biological effects in the ecosystem, whereas levels of the total WHO-TEQs were below threshold for sea food suggesting limited risks for humans. No significant relationships between levels of DLC (expressed as WHO-TEQ), and biological responses such as the induction of CYP1A enzymatic activity and fry reproductive disorders were observed in eelpout. No marked relationship between WHO-TEQ and combined biological aryl hydrocarbon receptor-mediated transactivity (expressed as AhR-TEQ) was noted. However, there was a positive correlation between polycyclic aromatic hydrocarbon (PAH) metabolites and induction of CYP1A activity, suggesting that PAH exhibited greater potential than DLC to produce biological effects in eelpout from the Baltic Sea.